Narrative Obtrusion in the Hebrew Bible. - Paris, Christopher T. (Emerging scholars., 2014)
Narrators of the Hebrew Bible generally allow their stories to proceed while relying on characters and dialogue to provide necessary information. Paris calls attention to when the story teller "breaks frame" to provide information or direct reader understanding, preventing undesirable construals or interpretations of the story. After surveying the phenomenon in the Hebrew Bible and other ancient Near Eastern literature, Paris focuses on the Deuteronomistic History. Paris argues that attention to narrative obtrusion offers an entry point into the world of the narrator and redefines aspects of n.